Genetic parameters and selection gains in open-pollination progenies of bacabi palm tree (Oenocarpus mapora) - da Silva Bronze, Antonia Benedita; Monteiro, Harleson Sidney Almeida [UNESP]; de Nazaré Santana Brito, Sinara [UNESP]; Pinheiro, Valdeci Junior Fonseca; Monteiro, Sabrina Gomes; de Almeida Abreu, Layse Barreto; Lima, Valdeides Marques; da Costa Mota, Milton Guilherme (Lepidus Tecnologia, 2024)
The Bacabi (Oenocarpus mapora Karsten) is an Amazonian palm whose fruit is widely used in the food industry due to its organoleptic properties and excellent nutritional quality. The objective of this work was to estimate genetic parameters and selection gains in the selection of open pollinated bacabi progenies. The experiment was carried out in the district of Campo Limpo, in the municipality of Santo Antônio do Tauá, state of Pará. The study assessed 38 progenies from open-pollination under an agroforestry system in a randomized block design with five replicates and two plants per plot. At Seventeen, Twenty-four and Thirty months after planting, data were collected on the following traits: stem height (SH), plant diameter (DIAM), number of live leaves (NLL), length of the leaf rachis (LLR), number of leaflet pairs (NLP) and leaflet length (LL). Genetic variety was observed among and within progenies for all evaluated traits. The broad-sense heritability estimates varied between 0.13 and 72.81%. High values were found for NLP (72.81%), DIAM (52.01%), LLR (62.64%), and SH (66.16%). Selection gains can be achieved for all the traits evaluated, with selection of 30% among progenies and 20% inside progenies.
Keywords: Amazonian palm; Genetic differences; Native species; phytotechnics